Assessment of Economic Viability for PV Based hybrid Energy System in West Coast of Turkey (Global Journals of Research in Engineering, 2012)
In this paper, a pre-feasibility study of using PV-based hybrid energy system to provide electricity to a residential area in west coast of Turkey is examined. The selected case study represents a power demand of 12.6kWh day-1 with a 2.9 kW peak power demand. The power system used in this study contains diesel generator, grid connection and PV modules with backup storage. The energy system was redesigned and optimized as PV based in order to meet the existing user#x2019;s power demand at a minimum cost of energy. Temperature and solar radiation data obtained from Ege University meteorology station has been used in the simulation process through optimization software, HOMER. Three systems that were considered in this study area are stand-alone PV-diesel, stand-alone PV-battery and grid connected PV system. The proposed systems then were compared regarding on their operational characteristics and cost values. The comparisons prove that grid connected PV energy system had the lowest total net present cost and cost of energy, $53,197 and $0.57/kWh, respectively that makes it the most cost effective system and followed by PV-diesel and stand-alone PV-battery system. It can be concluded that the renewable-based system can become a favorable system without aid from the grid system and bring advantage in technical and economic point of view and also suitable to be applied in the residential application as energy supply if only the current cost of PV arrays and battery system technology have been reduced to its minimum rate.
Keywords: photovoltaic; renewable energy; hybrid system